Seroprevalence of hepatitis B antibodies among international and domestic university students. Issue 10 (8th August 2021) - Heywood, Anita; Dyda, Amalie; Hu, William; Saha, Amit; Mahimbo, Abela; Gidding, Heather; Kefalas, Bill; Seale, Holly; Macintyre, C. Raina; Zwar, Nicholas; Rawlinson, William
Abstract: Chronic hepatitis B prevalence is low in most Australian populations, with universal infant HBV vaccination introduced in 2000. Migrants from high prevalence countries are at risk of acquisition before arrival and non‐immune adults are potentially at risk through skin penetrating procedures and sexual contact, particularly during international travel. The risk profile of young adult students, many from high prevalence countries, is inadequately understood. A cross‐sectional online survey conducted among university students collected data on demographic, vaccination and travel characteristics and blood samples were tested for hepatitis B surface antibody (HBsAb) and hepatitis B core antibody (HBcAb). Analyses identified factors associated with HBsAb seroprevalence and self‐reported vaccination. The serosurvey was completed by 804 students born between 1988 and 1993, with 613/804 (76.2%, 95% CI 73.2–79.1) self‐reporting prior HBV vaccination. Overall, 526/804 (65.4%, 95% CI 62.0%–68.6%) students were seropositive to HBsAb, including 438/613 (71.5%, 95% CI 67.8–74.9) students self‐reporting a prior HBV vaccine and 88/191 (46.1%, 95% CI 39.2–53.2) students self‐reporting no prior HBV vaccine. Overall, 8/804 (1.0%, 95% CI 0.5%–2.0%) students were HBcAb positive, of whom 1/804 (0.1%, 95% CI 0.02%–0.7%) was currently infectious. The prevalence of chronic HBV infection was low. However, more than one in four students were susceptible to HBV and over‐estimated their immunity. Future vaccination efforts should focus on domestic students born before the introduction of the infant program and all international students. Screening and vaccination of students, including through campus‐based health services, are an opportunity to catch‐up young adults prior to undertaking at‐risk activities, including international travel.